RK‐287107, a potent and specific tankyrase inhibitor, blocks colorectal cancer cell growth in a preclinical model. Issue 12 (20th October 2018) - Mizutani, Anna; Yashiroda, Yoko; Muramatsu, Yukiko; Yoshida, Haruka; Chikada, Tsubasa; Tsumura, Takeshi; Okue, Masayuki; Shirai, Fumiyuki; Fukami, Takehiro; Yoshida, Minoru; Seimiya, Hiroyuki
Abstract : Aberrant activation of Wnt/β‐catenin signaling causes tumorigenesis and promotes the proliferation of colorectal cancer cells. Porcupine inhibitors, which block secretion of Wnt ligands, may have only limited clinical impact for the treatment of colorectal cancer, because most colorectal cancer is caused by loss‐of‐function mutations of the tumor suppressor adenomatous polyposis coli (APC) downstream of Wnt ligands. Tankyrase poly(ADP‐ribosyl)ates (PARylates) Axin, a negative regulator of β‐catenin. This post‐translational modification causes ubiquitin‐dependent degradation of Axin, resulting in β‐catenin accumulation. Tankyrase inhibitors downregulate β‐catenin and suppress the growth of APC‐mutated colorectal cancer cells. Herein, we report a novel tankyrase‐specific inhibitor RK‐287107, which inhibits tankyrase‐1 and ‐2 four‐ and eight‐fold more potently, respectively, than G007‐LK, a tankyrase inhibitor that has been previously reported as effective in mouse xenograft models. RK‐287107 causes Axin2 accumulation and downregulates β‐catenin, T‐cell factor/lymphoid enhancer factor reporter activity and the target gene expression in colorectal cancer cells harboring the shortly truncated APC mutations. Consistently, RK‐287107 inhibits the growth of APC‐mutated (β‐catenin‐dependent) colorectal cancer COLO‐320DM and SW403 cells but not the APC‐wild (β‐catenin‐independent) colorectal cancer RKO cells. Intraperitoneal or oral administration of RK‐287107 suppresses COLO‐320DM tumor growth in NOD‐SCID mice. Rates of tumor growth inhibition showed good correlation with the behavior of pharmacodynamic biomarkers, such as Axin2 accumulation and MYC downregulation. These observations indicate that RK‐287107 exerts a proof‐of‐concept antitumor effect, and thus may have potential for tankyrase‐directed molecular cancer therapy. Abstract : Aberrant activation of Wnt/β‐catenin signaling causes tumorigenesis and promotes the proliferation of colorectal cancer cells. We report a novel tankyrase‐specific PARP inhibitor RK‐287107, which inhibits tankyrase‐mediated PARylation of Axin and downregulates β‐catenin signaling in APC‐mutated colorectal cancer cells. RK‐287107 exerts a proof‐of‐concept antitumor effect in vivo, and thus may have potential for cancer therapy.